2000
DOI: 10.1038/35041515
|View full text |Cite
|
Sign up to set email alerts
|

New high-pressure phases of lithium

Abstract: Lithium is considered a 'simple' metal because, under ordinary conditions of pressure and temperature, the motion of conduction electrons is only weakly perturbed by interactions with the cubic lattice of atomic cores. It was recently predicted that at pressures below 100 GPa, dense Li may undergo several structural transitions, possibly leading to a 'paired-atom' phase with low symmetry and near-insulating properties. Here we report synchrotron X-ray diffraction measurements that confirm that Li undergoes pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

30
345
1
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 359 publications
(378 citation statements)
references
References 23 publications
30
345
1
2
Order By: Relevance
“…For the metallic fcc phase, we find IEs located at octahedral interstices between Li þ ions (six coordinate), whereas in the semimetallic cI16, half of the IEs are located inside trapezoidal zigzag chains in the (010) direction, with the other half sitting in between ions bridging the chains (eight coordinate but with four shorter bonds). These locations are identical to the electron density maxima observed in DFT calculations (10).…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…For the metallic fcc phase, we find IEs located at octahedral interstices between Li þ ions (six coordinate), whereas in the semimetallic cI16, half of the IEs are located inside trapezoidal zigzag chains in the (010) direction, with the other half sitting in between ions bridging the chains (eight coordinate but with four shorter bonds). These locations are identical to the electron density maxima observed in DFT calculations (10).…”
Section: Resultssupporting
confidence: 71%
“…Such predictions stimulated X-ray diffraction experiments of compressed Li (10), that found a transition from fcc (CN 12) to the cI16 (CN 11) structure in which each electron is close to eight nuclei. This was followed by further DFT studies showing the cI16 (9, 21-24) structure to be stable at high P and low T Author contributions: H.K., J.T.S., and W.A.G.…”
mentioning
confidence: 99%
“…Although it could be expected to evolve to an even more free-electron like system with increasing pressure, it has been shown that pressure not only induces several structural transformations [2,3,4], but also gives rise to a plethora of fascinating physical properties [5] normally induced by nonlocality in the core pseudopotential with pressure [6,7]. For instance, lithium becomes a semiconductor near 80 GPa [8], it melts below ambient temperature (190 K) at around 50 GPa [2] and displays a periodic undamped plasmon according to theoretical calculations [9].…”
Section: Introductionmentioning
confidence: 99%
“…On further compression, there is a transition to a body-centred cubic structure with 16 atoms per unit cell (cI16) at 103 GPa [30], followed by transitions to a number of very complex phases above that pressure [31,32]. The cI16 structure had already been determined in lithium, where it exists above 40 GPa at 180 K [33] and is shown in figure 3. It has space group I43d with 16 atoms on a 16c site, (x, x, x), and refinements of powder diffraction data for Li gave a value of 0.055(1) for x at 46 GPa and 180 K. The cI16 crystal of Na was prepared by compressing a powdered sample of Na to 108 GPa, followed by careful annealing just below the melting curve at 313 K. The diffraction data were collected on an image-plate detector in a sequence of contiguous ±0.25 • oscillations over a total scan range of 14 • around the vertical axis using an X-ray wavelength of 0.3444 Å.…”
Section: Example 1: First Single-crystal Diffraction Above 100 Gpamentioning
confidence: 99%